Satisfaction of E-Learners with Electronic Learning Service Quality Using the SERVQUAL Model - Razia Sultana Sumi; Golam Kabir (Journal of Open Innovation: Technology, Market and Complexity, 2021)
ABSTRACT: Electronic learning (E-learning) is an innovative learning tool that provides an opportunity for technology-driven distance teaching. E-learning not only enhances learning quality, but it has also become the only medium of learning during the COVID-19 pandemic, when people have been forced to stay at home. Due to the pandemic, most countries have initiated online learning to continue the learning process, thus lessening the study gap. Against this backdrop, it is imperative to explore the perception and satisfaction level of e-learners regarding e-learning tools. In this study, a quantitative approach was conducted on the students of two leading public universities (graduates and postgraduates) to identify the impact of the determinants of the SERVQUAL model (reliability, responsiveness, assurance, empathy, and website design), as well as ‘learning content’, on overall perceived quality and satisfaction. In total, 895 respondents participated in the study, and data were analyzed with Amos 23 to confirm the hypotheses, utilizing structural equation modeling. The findings reveal that all the variables of the measurement model had a significant effect on perceived service quality and thus user satisfaction except for responsibility. The results make a significant contribution to those decision-makers and university authorities attempting to ensure e-learners’ satisfaction.